2019
DOI: 10.11591/ijere.v8i3.20252
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the mastery of research statistical concept by using problem-based learning

Abstract: The consequence of the assessment for the research statistics course at the department of physics Education in Universitas Jambi demonstrates the students' capacities to hold the idea of the mastery of research statistical concept is very low. It winds up one of the shortcomings for them to finish their final assignment. Therefore, the researcher examined the student's mastery of the research statistical concept by utilizing Problem-Based Learning as one of the methods that were chosen from the learning advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Mastery of concepts can be trained, one of which is through a learner-centered learning process by directing students to be active by using a scientific approach, this is in accordance with the results of research conducted by Fitriani (2016) and Susbiyanto et al (2019) who found that learning using a scientific approach can make students focused to be able to find concepts and apply concepts creatively through their activities or in work groups. Problem solving skills can also be trained through providing direct experience to students by giving work orders in the form of sheets contained in the SW, this is in accordance with the results of research conducted by Elwi et al (2017) and Meutia et al (2021) who found that learning using SW can make students motivated and active in learning physics which leads students to find concepts in understanding the material.…”
Section: Introductionsupporting
confidence: 83%
“…Mastery of concepts can be trained, one of which is through a learner-centered learning process by directing students to be active by using a scientific approach, this is in accordance with the results of research conducted by Fitriani (2016) and Susbiyanto et al (2019) who found that learning using a scientific approach can make students focused to be able to find concepts and apply concepts creatively through their activities or in work groups. Problem solving skills can also be trained through providing direct experience to students by giving work orders in the form of sheets contained in the SW, this is in accordance with the results of research conducted by Elwi et al (2017) and Meutia et al (2021) who found that learning using SW can make students motivated and active in learning physics which leads students to find concepts in understanding the material.…”
Section: Introductionsupporting
confidence: 83%
“…Each class has its way (posture) to do the practicum. Attitude to learning is important, so even with the existing attitude to learning about college courses [27]. Students in the experimental class are also capable of using direct e-module in the laboratory without demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Glancy, et al [44] observed that students struggle in data analysis manifesting difficulty in using certain measurement devices as well as interpretation of test of significance. In addition, Susbiyanto, et al [45] showed that problem-based learning affects the mastery of research statistical concept. Moreover, this finding is parallel to the findings of the explorative study from abroad conducted by Sismono, et al [46] among junior high school secondary mathematics teachers which revealed that the difficulty of teachers in problem solving lay in determining the precise mathematical model which in turn explains why teachers had difficulty in identifying the appropriate statistical tool to be applied in data analysis.…”
Section: Competency Level Of Mathematics Teachers In Organizing the R...mentioning
confidence: 99%